Synthesis and Characterization of New 3-Cyano-2-Pyridone Derivatives as Fluorescent Scaffolds - Asmaa Kebaili; Fatima Belhadj; Zahira Kibou; Julio A. Seijas; M. Pilar Vazquez Tato; Noureddine Choukchou-Braham (Chemistry Proceedings)
2-pyridones are among the most widely used nitrogen-containing heterocyclic derivatives in various fields due to their structural properties and biological and therapeutic activities. Therefore, their synthesis has become a major focus of organic chemistry in recent years. In this context, we are interested in the synthesis of N-alkyl-3-cyano-2-pyridones and their derivatives. This work describes a new synthetic method that allows easy and efficient access to these structures under mild conditions through a simple study of their fluorescence applications.